Live from the Ryman and more [compact disc] - Crow, Sheryl (Valory, 2021)
Sheryl Crow has defined the essential place of a woman in rock since releasing her seven times platinum-certified Tuesday Night Music Club and self-titled Best Rock Album Grammy-winning follow-up. With rock n' roll is at its best live and at a time when concerts are suspended, Crow delivers a 27-song set captured live in 2019 at Nashville's historic Ryman Auditorium, Los Angeles's cutting-edge Ace Theatre, and the legendary Newport Folk Festival in Rhode Island.